2001
DOI: 10.1109/mper.2001.4311579
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Digital Simulation of Power Electronic Apparatus Interfaced with Digital Controllers

Abstract: This paper presents a new approach for the real-time digital simulation of power electronic controllers in power systems. Digital controllers for power electronic systems present a problem when testing in real-time using a digital simulator due to the discrete nature of their outputs which are not necessarily in synchronism with the time step of the simulator. The proposed algorithm combines the variable step-size numerical integration method with linear interpolation for the synchronization of a real-time dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 5 publications
0
14
0
1
Order By: Relevance
“…2 The application of the backward-Euler method to discretize (1) yields: (6) Thus, the following associated discrete circuit model is obtained with the backward-Euler method:…”
Section: A Associated Discrete Circuit Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The application of the backward-Euler method to discretize (1) yields: (6) Thus, the following associated discrete circuit model is obtained with the backward-Euler method:…”
Section: A Associated Discrete Circuit Modelmentioning
confidence: 99%
“…T HE RAPID progress in computer hardware performance and the creation of both efficient and accurate simulation algorithms have contributed to the development of real time digital simulators [1]- [6]. In real time simulation for equipment testing, the simulation time advances at the speed of the real time so that results are output in synchronism with the real time clock.…”
Section: Introductionmentioning
confidence: 99%
“…By using the full-digital simulator, the engineers can achieve a small size and flexible tuning simulation environment. Thus, the real-time simulation has become a famous technique [1][2][3][4] in designing a power electronics circuit. The merits and the drawbacks of a digital real-time simulator are summarized in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…In such cases a 50 time-step is no longer acceptable since it becomes difficult to account for switching events that occur between two calculation steps in the simulation. It has been shown that [22] inaccurate accounting of switching events results in significant errors in the fundamental and characteristic harmonics, as well as in the generation of non-characteristic harmonics. The choice of time-step in power electronic system simulation is dictated by the switching frequency and the complexity (number of switches) in the system.…”
Section: Introductionmentioning
confidence: 99%